THE ADVANTAGES OF TEACHING ENGLISH LANGUAGE THROUGH ONLINE PLATFORMS OF HIGHER EDUCATION INSTITUTIONS (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
This article is devoted for the benefits of online educational platforms of teaching English language in higher education institutions as well as the facilities that both teachers and students of higher education institutions can have. And, educational technologies in use will be reviewed.